Menakar Fungsi Organisasi Perempuan Dalam Persepektif Kesetaraan Gender - Dwi Astuti (FKIP, Universitas Palangka Raya, 2021)
Women’s organization are one of the instrument that are considered capable to fighting for gender equality. However, it was found that many women’s organization were have wrong interpreting about the role of their existence. So, even tought women’s organization have been active for decades, they have not had a significant impact on efforts for gender equality in Indonesia. this can be seen form the low gender development index in Indonesia compared to several countries in the world. This study aims to look at and reflect the existence of women;s organization in Indonesia, and try to indentify what iportant aspect of women’s organization that affect ti gender equality. This research uses discriptive qualitatif method. They key to reach the success of women’organization in striving for gender equality lies in the perspective and on the programm of women’s organization in understanding their roles. There are many women’s organization in Indoensia with various form, types, acitvities and membership backgrounds. However, whatever the form of organization and its field work, the key to success in realizing gender equality, is when women’s organization focus on identifying women’s needs, reflecting and reconstructing patriarchal hegemony, strengthening skill and knowledge, incerasing access to policies, empowering women, networking and knowing women’s issues in the global realism.